How Do Upper Echelons Perceive Porter’s Five Forces? Evidence From Strategic Entrepreneurship in China - Shi, Chengqi; Agbaku, Comfort Afi; Zhang, Fan (Frontiers in Psychology, 2021)
Porter’s five forces model is an authoritative management tool used in analyzing the profitability and attractiveness of industries through an outside-in viewpoint. In the past decade, dramatic and rapid changes have prompted some criticism of the model. The comparison between new and old economy analysis makes the fundamentals of the model seem weak. Moreover, the past decade has shown that strategy and entrepreneurship in China are not completely dependent on the model. This paper first aims to verify the sustainability of the five forces model and analyze its integration into China’s entrepreneurial economy. By conducting in-depth interviews among the upper echelons from various industries, it was found that along with the competitive factors emphasized by the model, Chinese entrepreneurs attend to cooperative factors such as Guanxi, the Chinese term for relationship, and the possibilities of technology integration with the five forces. They also tend to enlarge the strategic view to consider factors such as how the market evaluates the forces. To verify these findings, the authors carried out a large-scale survey with a modified questionnaire analyzing the collected data using Exploratory Factor Analysis with SPSS 22. The outcome shows that Porter’s model is still valid to some extent. Companies are still working in a network of buyers, suppliers, substitutes, new entrants, and competitors. However, re-inventions are necessary to include in the new factors of Guanxi, technology (e-commerce and logistics) and, marketing and branding, which have changed the structure of industry. These factors arise from the cooperative nature of Chinese culture and may have equal or even larger significance compared with their competitive counterparts in today’s business world.